Now first looking at the terms, the first thing I instinctively did was, I took y=x+1..so now the equation reduces to 1+16/(x*(x+1))+6(2x+1)..The function will be increasing in the interval (0,1) and after 1. So the minimum is obtained at x=1 which is 27

minimum value occurs..when x=2 y=1 or y=2 x=1…
the expression equals 27…for any other positive value the expression is greater than this….
Let x=ky
1/(y^2(k-1)^2)+ 16/(K*y^2)+ 6y(k+1)
we can try substituing values for K and Y….

I dont think this is best approach…just trial and error

RT @Nesenag: Support #Jayalalithaa you are supporting a cult leader, support Modi you are a Bhakt but being a doormat of fake Gandhis makes… 4 days ago

RT @abhijitmajumder: Tariq Anwar made up Murthal rapes. All media lies abt church attacks fell flat. Intelligentsia used both, never retrac… 4 days ago

Now first looking at the terms, the first thing I instinctively did was, I took y=x+1..so now the equation reduces to 1+16/(x*(x+1))+6(2x+1)..The function will be increasing in the interval (0,1) and after 1. So the minimum is obtained at x=1 which is 27

Celebrating LifeOctober 8, 2008 at 6:43 am

Oops interchanged x and y..I considered 1/(y-x)^2

Celebrating LifeOctober 8, 2008 at 6:48 am

minimum value occurs..when x=2 y=1 or y=2 x=1…

the expression equals 27…for any other positive value the expression is greater than this….

Let x=ky

1/(y^2(k-1)^2)+ 16/(K*y^2)+ 6y(k+1)

we can try substituing values for K and Y….

I dont think this is best approach…just trial and error

AnkajOctober 8, 2008 at 2:37 pm